The relationship between knowledge and attitude of mothers towards infant massage aged 0-12 months in the working area of the Kuta Baro health center in Aceh - Fauziah, Fauziah; Jubir, Jubir; Sakdah, Nurul; Andriani, Irma; Nisa, Raiyatul (Jurnal EduHealth, 2024)
Efforts to improve the health and stimulation of the baby's growth and development that can be done independently by the mother is to provide touch stimulation through baby massage. Factors that influence the management of infant massage by mothers include internal and external factors. There are several factors related to infant massage including the knowledge factor where the mother's extensive knowledge will also affect the mother's desire to do baby massage, besides that there are also work factors, attitudes and perceptions that can influence the mother to do baby massage. This study aims to determine the relationship between knowledge and attitudes of mothers towards infant massage aged 0-12 months in the working area of the Kuta Baro Health Center. This type of research is quantitative with cross sectional design. Data collection used a questionnaire which was conducted from 08 March to 04 April 2023. The population in this study was mothers who had babies aged 0-12 months in the working area of the Kuta Baro Health Center totaling 427, using a proportional random sampling technique of 81 people. Data analysis used chi square with the results of the study showing that there was a relationship between knowledge (p=0.012) and attitude (p=0.046) with baby massage it is expected that families can stimulate (stimulate) baby breasts which are very useful in stimulating muscles in babies so that children can grow and growing well.